A 3D intestinal tissue model supports Clostridioides difficile germination, colonization, toxin production and epithelial damage. (April 2018) - Shaban, Lamyaa; Chen, Ying; Fasciano, Alyssa C.; Lin, Yinan; Kaplan, David L.; Kumamoto, Carol A.; Mecsas, Joan
Abstract: Endospore-forming Clostridioides difficile is a causative agent of antibiotic-induced diarrhea, a major nosocomial infection. Studies of its interactions with mammalian tissues have been hampered by the fact that C. difficile requires anaerobic conditions to survive after spore germination. We recently developed a bioengineered 3D human intestinal tissue model and found that low O2 conditions are produced in the lumen of these tissues. Here, we compared the ability of C. difficile spores to germinate, produce toxin and cause tissue damage in our bioengineered 3D tissue model versus in a 2D transwell model in which human cells form a polarized monolayer. 3D tissue models or 2D polarized monolayers on transwell filters were challenged with the non-toxin producing C. difficile CCUG 37787 serotype X (ATCC 43603) and the toxin producing UK1 C. difficile spores in the presence of the germinant, taurocholate. Spores germinated in both the 3D tissue model as well as the 2D transwell system, however toxin activity was significantly higher in the 3D tissue models compared to the 2D transwells. Moreover, the epithelium damage in the 3D tissue model was significantly more severe than in 2D transwells and damage correlated significantly with the level of toxin activity detected but not with the amount of germinated spores. Combined, these results show that the bioengineered 3D tissue model provides a powerful system with which to study early events leading to toxin production and tissue damage of C. difficile with mammalian cells under anaerobic conditions. Furthermore, these systems may be useful for examining the effects of microbiota, novel drugs and other potential therapeutics directed towards C. difficile infections. Graphical abstract: Highlights: A bioengineered 3D tissue model provides an anaerobic environment to support studying C. difficile in vitro . A significantly higher toxin activity is detected in the 3D tissue model infected with toxigenic C. difficile . More severe damage to the epithelial tissue is observed in the 3D tissue model infected with toxigenic C. difficile . Epithelial damage correlated significantly with the level of toxin activity in both models, but did not correlate with CFU.